Comparison of curcumin with intralesional steroid injections in Oral Submucous Fibrosis – A randomized, open-label interventional studyKey message - Monu Yadav; K. Aravinda; Vasu S. Saxena; K. Srinivas; P. Ratnakar; Jyothi Gupta; Arti Saluja Sachdev; Peeyush Shivhare (Journal of Oral Biology and Craniofacial Research)
Introduction: Oral Submucous Fibrosis (OSMF) is precancerous condition caused by areca nut chewing characterized by restricted mouth opening, burning sensation and stiffness & blanching of oral mucosa. Complete regression of the condition had not been achieved in all cases with any of the present treatment regimens. Curcumin is (diferuloylmethane), a yellow pigment in curry powder, exhibits anti-oxidant, anti-inflammatory, and pro-apoptotic activities. Hence an interventional study was undertaken to establish the efficacy of curcumin in OSMF patients. Settings & design: A randomized open label, interventional study was conducted in forty patients with clinically and histologically proven Oral Submucous Fibrosis. Materials & methods: Forty patients with clinically and histologically proven Oral Submucous Fibrosis were selected for the study and were randomly divided into 2 groups. The first group was treated with weekly intralesional injection of 4 mg Dexamethasone & 1500 I.U Hyaluronidase and the second group by oral administration of two Curcumin tablets (Turmix 300 mg) per day for 3 months each. Improvement of burning sensation, interincisal distance and tongue protrusion was evaluated on a weekly basis. Results: Burning sensation improved in both the groups from early to late stages. Complete resolution of burning sensation was noted with turmix. The mean increase in interincisal distance was 3.13 mm and 1.25 mm respectively in groups 1 &2. The interincisal distance improved in both the groups, with significant results at the end of first month. Tongue protrusion showed greater recovery at the end of 1st month in group 1 when compared with group 2. Conclusion: Turmix is beneficial and effective in reducing burning sensation in early OSMF patients.